Obstacles in Responsible Character Education for Grade 4 Elementary School Students during the Covid-19 Pandemic: Hambatan dalam Pendidikan Karakter Tanggung Jawab pada Siswa Kelas 4 Sekolah Dasar di Masa Pandemi Covid-19 - Rismawati, Diah; Wardana, Mahardika Darmawan Kusuma (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to determine the barriers to learning responsibility for character education in an elementary school located in Sidoarjo Regency. The approach used in this research is qualitative phenomenology with the type of case study research. The subjects in this study were fourth grade students at SDN Kedungcangkring. Based on the results of the study, it was concluded that in planning schools for character education, responsibility had been prepared during the covid-19 pandemic, but had several obstacles that occurred. This can be seen from the results of the study which show that the implementation of character education for students' responsibility in schools is still hampered by factors from the students themselves and the environment around them.